FEATURES OF ACCOUNTING AND FINANCIAL CONTROL IN SMALL BUSINESS - Sirojiddinov Ikromiiddin Qutbiddinovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article examines the most important features of accounting and financial control in small businesses.